THE NATURE OF RESOURCE-SAVING TECHNOLOGIES AND FEATURES OF THEIR USE IN COTTON FARMING - Sidikov Dilmurod Hasanboy oglu; Rashidov Rahmatullo Alojonovich (Galaxy International Interdisciplinary Research Journal, 2022)
The importance of the role of the cotton sector in the economy of the republic is that this sector supplies raw materials for other sectors of the economy and is a consumer of the manufacturers of industrial products used in the sector. It has an important socio-economic importance in providing employment to the population living in rural areas and income to their families.